Control synthesis for 4WS vehicle-robot model for traffic program motion - Tatievskyi, Dmitry (Technology audit and production reserves, 2019)
The object of research is an autonomous wheeled mobile robot model 4WS (Four Wheel Steering). The need for such studies is dictated by the limitations of using 2WS (Two Wheel Steering) robots to solve the problem of achieving multiple goals associated with insufficient maneuverability and traffic safety. This is one of the most problematic places of this model. Such a task was successfully solved to achieve a single goal with this model, including reverse movements for an articulated crew, but the nature of the trajectory with multiple goals makes such a task practically unsolvable. To solve it, the design of the autonomous mobile robot DDMR model was successfully applied. The advantages of the 4WS model compared to the 2WS in terms of increasing maneuverability have led to the study of the possibility of using it to solve this problem. In this study, the possibility of synthesizing the controlled movement of an autonomous mobile robot of the 4WS model along a program path specified in an explicit, implicit, parametric form or by the law of change in its curvature is realized. In this case, the angle of rotation of the front wheels is a function of the curvature of the program path, and the rear wheels are a function of the angle of rotation of the front. A feature of synthesized control for the 4WS model is the connection with control for the 2WS model. Control for this model is synthesized initially and is an independent value. Such a reference control: the empirical dependence determines the virtual radius for which such a control is calculated for the 4WS model so that it moves along the path of the 2WS model. The rotation of the rear wheels (in phase with the front or out of phase) is considered in this case as an additional control. An important feature of the study was the development of software that made it possible to perform numerical modeling of the synthesized control in the Maple mathematical package and visualization of maneuvers of movement in the Unity 3D system. The results of numerical modeling and their visualization allow to conclude that it is possible to use the synthesized law to control autonomous mobile robots created using the 4WS model.